Coolest Student Papers at Finland Futures Research Centre 2024–2025. Tulevaisuuden tutkimuskeskuksen valittuja opiskelijatöitä 2024–2025. - Aalto, Hanna-Kaisa; Arvonen, Anne; Heino, Hanna; Keski-Pukkila, Pasi; Haapanen, Liisa; Puustinen, Sari; Pöllänen, Markus; Shaw, Morgan; Siivonen, Katriina; Tapio, Petri; Taylor, Amos; Wilenius, Markku (Turun yliopisto, 2026)
Finland Futures Research Centre has been publishing since 2016 a collection of the most prominent student papers written during their studies. The FFRC aims to provide a genuine publication forum for students and help them achieve their first publication entry. In times when the appreciation of science and scientific knowledge is at risk, the skill of academic writing is more important than ever. We want to help our students develop their writing skills. AI also requires information for processing, and we hope that our publication serves that need as well.
Our publication consists of writings by students from the Master's Program in Futures Studies, Sustainable Development Studies at the University of Turku, and Finland Futures Academy. Since student papers are originally written in either Finnish or English, we publish them in their original language. The papers address multiple questions related to current challenges, similar to those explored in our courses. The students have eagerly participated in choosing the topics for their writings in various courses, demonstrating their interest in global challenges and the role of science in addressing them.